(untitled) (Journal of Engineering, 2011)
The performance grading system (superpave) has provided means to incorporate binder characteristics with pavement failure types. It’s a comprehensive system that relates climate, traffic conditions and aging with critical pavement distress. The objective of this paper is to develop an improved asphalt binder grading system for Iraq based on the principal of superpave. The country was divided into different zones according to the highest and lowest temperature ranges and traffic loading. The Performance graded binder proposed for each zone was compared with some States of USA that have same hot weather of Iraq by using Long Term Pavement Performance (LTPP v3.1) software. Iraqi asphalt samples were tested using the Superpave technology in Wisconsin University and the results were compared with those estimated using Shell pavement design software packages (BANDS 2) at different loading time and frequency. In general, the performance grade of binders produced from the three refineries in Iraq (Daurah, Basrah and Baiji) is PG 64-16. The m- value (slope of log creep stiffness versus log frequency curve at specified temperature) determined by DSR (Dynamic Shear Rheometer) and Shell software was compared.